Determinants of The Resilience of The Muslim Fashion Industry During the Covid-19 Pandemic - Yuda Septia Fitri; Vemy Suci Asih; Dudang Gojali (UPT Publikasi Ilmiah UNISBA, 2026)
This study examines the factors that supported the resilience of Muslim fashion micro, small, and medium enterprises (MSMEs) during the COVID-19 pandemic, a period in which the sector remained viable and continued to expand as a promising business opportunity. Using a quantitative explanatory design, the research analyzes how digital marketing, pricing, and design contribute to business resilience. Primary data were collected through a structured questionnaire administered to 87 Muslim fashion entrepreneurs in Bandung, West Java, Indonesia, who had operated continuously from 2018 to 2021. Respondents were selected using probability-based simple random sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to estimate the relative effects of the three determinants. The results indicate that digital marketing provides the strongest positive contribution to resilience (β = 0.434), particularly through the use of websites, social media, and email. Pricing strategies also show a significant positive effect (β = 0.253), reflecting the importance of competitive prices, discounts, and affordability in maintaining customer demand under economic constraints. Design contributes positively as well (β = 0.190), emphasizing the role of trend alignment, designer input, and product uniqueness. Overall, the study offers empirical evidence that digital marketing is the most influential driver of resilience, followed by price and design. These findings inform policymakers and industry stakeholders seeking targeted interventions to strengthen the adaptive capacity of Muslim fashion MSMEs in times of disruption and uncertainty.